Tinjauan Hukum Islam Terhadap Praktik Hibah Hareuta Peunulang di Aceh - Usman, Munadi (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2020)
In Acehnese society, there is a tradition called hareuta peunulang, which is the practice of giving a number of assets to married girls in preparation for starting a new life with her husband. This practice is still often carried out until now, especially by people in the Pidie Regency, Aceh Besar District and parts of the West Aceh region. This practice seems to be gender-biased, which is more privileging girls and discriminating boys. This article wants to criticize the practice of hareuta peunulang grants using the theory of grants in Islamic law, with the aim of finding a contradiction between the two and offering several legal formulas to reconstruct these traditional institutions so that they are in line with the ideals of Islamic law. [Dalam masyarakat Aceh dikenal suatu institusi adat yang disebut hareuta peunulang, yaitu praktik penghibahan sejumlah harta untuk anak perempuan yang telah menikah sebagai bekal memulai kehidupan baru bersama suaminya. Praktik ini masih kerap dilakukan sampai sekarang, khususnya oleh masyarakat di wilayah Kabupaten Pidie, Aceh Besar dan sebagian wilayah Aceh Barat. Praktik ini terkesan bias gender, di mana lebih mengistimewakan anak perempuan dan mendiskriminasikan anak laki-laki. Artikel ini ingin mengkritisi praktik hibah hareuta peunulang menggunakan teori hibah dalam hukum Islam, dengan tujuan menemukan kontradiksi antara keduanya dan menawarkan beberapa formula hukum untuk merekonstruksi institusi adat tersebut supaya sejalan dengan cita hukum Islam.